2015
DOI: 10.1016/j.stemcr.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells Rescue Cognitive and Motor Dysfunction in a Transgenic Model of Dementia with Lewy Bodies through a BDNF-Dependent Mechanism

Abstract: SummaryAccumulation of α-synuclein (α-syn) into insoluble aggregates occurs in several related disorders collectively referred to as synucleinopathies. To date, studies have used neural stem cells (NSCs) to examine questions about α-syn propagation, but have overlooked the therapeutic potential of NSC transplantation to modulate cognition in disorders such as dementia with Lewy bodies or Parkinson’s disease dementia. Here, we show that striatal transplantation of NSCs into aged α-syn transgenic mice significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 50 publications
2
46
1
Order By: Relevance
“…Similarly, striatal transplantation of neural stem cells into a mouse model of dementia with Lewy bodies restores BDNF levels, thus improving AD-related motor and cognitive decline. In this study, transplanting BDNF-depleted neural stem cells did not improve behavior, while BDNF delivery via bilateral injection of adeno-associated virus mimicked the benefits of BDNF-expressing stem cells (Goldberg et al, 2015). Stem cell therapy has also been reported in mouse models of HD where mesenchymal stem cells benefits have been investigated (Olson et al, 2012).…”
Section: Modulating Bdnf Signaling In the Central Nervous Systemmentioning
confidence: 70%
“…Similarly, striatal transplantation of neural stem cells into a mouse model of dementia with Lewy bodies restores BDNF levels, thus improving AD-related motor and cognitive decline. In this study, transplanting BDNF-depleted neural stem cells did not improve behavior, while BDNF delivery via bilateral injection of adeno-associated virus mimicked the benefits of BDNF-expressing stem cells (Goldberg et al, 2015). Stem cell therapy has also been reported in mouse models of HD where mesenchymal stem cells benefits have been investigated (Olson et al, 2012).…”
Section: Modulating Bdnf Signaling In the Central Nervous Systemmentioning
confidence: 70%
“…It will be also informative to compare familial versus sporadic AD TAPs, and determine if specific familial AD mutations correspond to unique TAPs. Furthermore, a similar approach using iDISCO clearing should be easily transposable to any form of amyloidosis or related diseases, including non-AD dementias such as vascular dementia (O'Brien et al, 2015), frontotemporal dementia (Bang et al, 2015), dementia with Lewy bodies (Goldberg et al, 2015) and transmissible dementia (Watts et al, 2014; Sanders et al, 2016). This work also may have the potential to advance the evaluation strategies for therapeutic approaches in pre-clinical stages such as immunotherapies (Wisniewski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent study showed that striatal transplantation of neural stem cells into a mouse model of dementia with Lewy bodies improves motor and cognitive function by restoring BDNF levels. In this study, transplanting BDNF-depleted neural stem cells did not improve behaviour, whereas BDNF delivery via bilateral injection of adeno-associated virus mimicked the benefits of BDNF-expressing stem cells [72]. …”
Section: Alzheimer’s Diseasementioning
confidence: 99%